My First 5 Minutes Fairy Tales ; Hansel and Gretel - Om Books international (Bharat Om Books International, 2019)
Hansel and Gretel are lost in the forest when they see a cottage made of cakes, chocolates and candies. Who owns this cottage? This is a beautiful retelling of the classic children fairy tale - Hansel and Gretel. With vibrant, captivating illustrations and simple text, it will spark the child$1 (Bs imagination, develop speech & language skills, and encourage to read books.s
Keywords: Traditional Literature - Fairytales -- Traditional Literature - Fairytales